2011
DOI: 10.1097/ta.0b013e3181e59dbe
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Thermal Injury: No Sex-Related Difference

Abstract: There is no relevant sex-related difference in survival after thermal injury. The conclusion is, however, tempered by the few deaths, particularly among younger adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 26 publications
2
15
1
1
Order By: Relevance
“…Continued improvements in all aspects of the care of victims of burn injury have resulted in reported mortality rates showing marked improvement in developed countries from 54 to 100% at the beginning of the twentieth century to currently reported rates of around 4-6% [30][31][32][33][34][35]. This is attributed not only to advancements in the organisation, delivery and practice of burn care but also targeted efforts to prevent injuries [8].…”
Section: Discussionmentioning
confidence: 97%
“…Continued improvements in all aspects of the care of victims of burn injury have resulted in reported mortality rates showing marked improvement in developed countries from 54 to 100% at the beginning of the twentieth century to currently reported rates of around 4-6% [30][31][32][33][34][35]. This is attributed not only to advancements in the organisation, delivery and practice of burn care but also targeted efforts to prevent injuries [8].…”
Section: Discussionmentioning
confidence: 97%
“…Mortality increases with age and the size of the burn, and inhalation injury often worsens the prognosis [5,9,10,15,16]. The role of sex, however, is conflicting [5,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As well as age and size of burn, smoke inhalation injury has been shown to increase the risk of mortality, [41][42][43] while the results about the effect of sex are conflicting. [44][45][46][47][48][49] Clinical observations suggest that the patient's previous medical history plays an important part in the prognosis, and this has been confirmed in some large studies, but not in others.…”
Section: Prediction Of In-hospital Mortalitymentioning
confidence: 89%
“…34,45,47,63,64 However, risk-adjusted mortality may or may not be another difference between the sexes in burn care. 34,[45][46][47]65 A recent Swedish study in general intensive care showed equal mortality between men and women, but a different allocation of resources for the benefit of the men. 66 A female disadvantage in the level of medical care provided for general trauma and critical care patients has also been reported previously.…”
Section: Medical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation